Deoxyfluorination of acyl fluorides to trifluoromethyl compounds by FLUOLEAD®/Olah’s reagent under solvent-free conditions - Liang, Yumeng; Taya, Akihito; Zhao, Zhengyu; Saito, Norimichi; Shibata, Norio (Beilstein Journal of Organic Chemistry, 2020)
A new protocol enabling the formation of trifluoromethyl compounds from acyl fluorides has been developed. The combination of FLUOLEAD® and Olah’s reagent in solvent-free conditions at 70 °C initiated the significant deoxyfluorination of the acyl fluorides and resulted in the corresponding trifluoromethyl products with high yields (up to 99%). This strategy showed a great tolerance for various acyl fluorides containing aryloyl, (heteroaryl)oyl, or aliphatic acyl moieties, providing good to excellent yields of the trifluoromethyl products. Synthetic drug-like molecules were also transformed into the corresponding trifluoromethyl compounds under the same reaction conditions. A reaction mechanism is proposed.
Keywords: acyl fluorides; deoxyfluorination; fluorine; solvent-free; trifluoromethyl group

(untitled) - Isanbor, C.; O’Hagan, D. (J. Fluorine Chem., 2006)

(untitled) - Wang, J.; Sánchez-Roselló, M.; Aceña, J. L.; del Pozo, C.; Sorochinsky, A. E.; Fustero, S.; Soloshonok, V. A.; Liu, H. (Chem. Rev., 2014)

(untitled) - Zhu, Y.; Han, J.; Wang, J.; Shibata, N.; Sodeoka, M.; Soloshonok, V. A.; Coelho, J. A. S.; Toste, F. D. (Chem. Rev., 2018)

(untitled) - Inoue, M.; Sumii, Y.; Shibata, N. (ACS Omega, 2020)

(untitled) - Ogawa, Y.; Tokunaga, E.; Kobayashi, O.; Hirai, K.; Shibata, N. (iScience, 2020)

(untitled) - Nie, J.; Guo, H.-C.; Cahard, D.; Ma, J.-A. (Chem. Rev., 2011)

(untitled) - Landelle, G.; Panossian, A.; Leroux, F. R. (Curr. Top. Med. Chem., 2014)

(untitled) - Park, B. K.; Kitteringham, N. R.; O'Neill, P. M. (Annu. Rev. Pharmacol. Toxicol., 2001)

(untitled) - O’Hagan, D.; Harper, D. B. (J. Fluorine Chem., 1999)

(untitled) - Ma, J.-A.; Cahard, D. (J. Fluorine Chem., 2007)

(untitled) - Tomashenko, O. A.; Grushin, V. V. (Chem. Rev., 2011)

(untitled) - Cohen, O.; Mishani, E.; Rozen, S. (Tetrahedron, 2010)

(untitled) - Boswell, G. A., Jr; Ripka, W. C.; Scribner, R. M.; Tullock, C. W. (Org. React., 1974)

(untitled) - Shibata, N.; Mizuta, S.; Kawai, H. (Tetrahedron: Asymmetry, 2008)

(untitled) - Shibata, N.; Matsnev, A.; Cahard, D. (Beilstein J. Org. Chem., 2010)

(untitled) - Shibata, N. (Bull. Chem. Soc. Jpn., 2016)

(untitled) - Matsuzaki, K.; Hiromura, T.; Tokunaga, E.; Shibata, N. (ChemistryOpen, 2017)

(untitled) - Liang, Y.; Zhao, Z.; Shibata, N. (Commun. Chem., 2020)

(untitled) - Ogiwara, Y.; Sakai, N. (Angew. Chem., Int. Ed., 2020)

(untitled) - Munoz, S. B.; Dang, H.; Ispizua-Rodriguez, X.; Mathew, T.; Prakash, G. K. S. (Org. Lett., 2019)

(untitled) - Scattolin, T.; Deckers, K.; Schoenebeck, F. (Org. Lett., 2017)

(untitled) - Meanwell, M.; Lehmann, J.; Eichenberger, M.; Martin, R. E.; Britton, R. (Chem. Commun., 2018)

(untitled) - Gonay, M.; Batisse, C.; Paquin, J.-F. (J. Org. Chem., 2020)

(untitled) - Lal, G. S.; Pez, G. P.; Pesaresi, R. J.; Prozonic, F. M.; Cheng, H. (J. Org. Chem., 1999)

(untitled) - Lal, G. S.; Pez, G. P.; Pesaresi, R. J.; Prozonic, F. M. (Chem. Commun., 1999)

(untitled) - Keaveney, S. T.; Schoenebeck, F. (Angew. Chem., Int. Ed., 2018)

(untitled) - Hasek, W. R.; Smith, W. C.; Engelhardt, V. A. (J. Am. Chem. Soc., 1960)

(untitled) - Bugera, M.; Trofymchuk, S.; Tarasenko, K.; Zaporozhets, O.; Pustovit, Y.; Mykhailiuk, P. K. (J. Org. Chem., 2019)

(untitled) - Trofymchuk, S.; Bugera, M. Y.; Klipkov, A. A.; Razhyk, B.; Semenov, S.; Tarasenko, K.; Starova, V. S.; Zaporozhets, O. A.; Tananaiko, O. Yu.; Alekseenko, A. N.; Pustovit, Y.; Kiriakov, O.; et al. (J. Org. Chem., 2020)

(untitled) - Umemoto, T.; Singh, R. P.; Xu, Y.; Saito, N. (J. Am. Chem. Soc., 2010)

Ube Industries, Ltd

Sulfur Tetrafluoride. In Encyclopedia of Reagents for Organic Synthesis. [Online] Posted April 15, 2001. - Wang, C. L. J.

Trifluoro(N-methylmethanaminato)sulfur. In Encyclopedia of Reagents for Organic Synthesis. [Online] Posted May 27, 2014 - Champagne, P. A.; Paquin, J.-F.

(untitled) - Umemoto, T.; Singh, R. P. (J. Fluorine Chem., 2012)

4-tert-Butyl-2,6-dimethylphenylsulfur trifluoride. In Encyclopedia of Reagents for Organic Synthesis. [Online] Posted May 15, 2013 - Umemoto, T.

Pyridinium Poly(hydrogen fluoride). In Encyclopedia of Reagents for Organic Synthesis. [Online]; Posted March 15, 2007 - Kotun, S. P.; Prakash, G. S.; Hu, J.